2017
DOI: 10.1016/j.scitotenv.2016.11.140
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of improved water access in the context of schistosomiasis transmission in rural Eastern Region, Ghana

Abstract: Populations with poor access to water, sanitation and hygiene (WASH) infrastructure are disproportionately affected by the neglected tropical diseases (NTDs). As a result, WASH has gained increasing prominence in integrated control and elimination of NTDs, including schistosomiasis. In order to identify underserved populations, relevant measures of access to WASH infrastructure at sub–national or local levels are needed. We conducted a field survey of all public water sources in 74 rural communities in the Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Prior research in the Eastern Region suggests that groundwater sources are underutilized in part due to these WQ problems (Kosinski et al, 2016; Kulinkina et al, 2016). Undesirable organoleptic characteristics of groundwater from BHs are also likely linked to consumption of microbiologically and chemically contaminated surface water (Kulinkina et al, 2017), which can lead to substantial detrimental public health impacts. Examining geographic clustering of WQ problems and patterns in dynamic water consumption from multiple water sources using spatial analyses (Alarcon Falconi et al, 2017) can be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior research in the Eastern Region suggests that groundwater sources are underutilized in part due to these WQ problems (Kosinski et al, 2016; Kulinkina et al, 2016). Undesirable organoleptic characteristics of groundwater from BHs are also likely linked to consumption of microbiologically and chemically contaminated surface water (Kulinkina et al, 2017), which can lead to substantial detrimental public health impacts. Examining geographic clustering of WQ problems and patterns in dynamic water consumption from multiple water sources using spatial analyses (Alarcon Falconi et al, 2017) can be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study was excluded from ethical review because collected information pertained to water sources and not to the survey respondents. To design the WQ sampling and survey protocol, we used information gathered during the 2014 study (Kulinkina et al, 2017), which identified a total of 238 BHs in 67 communities. Of these, 176 BHs in 61 communities were functional and constituted the sample frame for this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations